Relationship between incidents occurred in the beach area and the presence of return current on beaches in the metropolitan region of São Luís, MA - Sila, Marcelo Victor Rodrigues da; Monteiro, Vitorya Mendes da Silva; Lima, Kaio Lopes de; Santos, Jadson Pinheiro; Silva, Camila Magalhães (Seven Editora, 2024)
Rip currents are known to be the biggest cause of rescues and drownings within the surf zone. In Australia, about 90% of all rescues carried out in the surf zone and the majority of drownings are related to rip currents (Short, 1999). The objective of the work was to make a relationship between rip currents and the incidents that occurred in the great island of São Luís. For the research, a survey of the accident record was carried out, images were obtained and awareness and information work was carried out. The interpellation of the data was applied in a participatory way, seeking the knowledge of all those who were involved in the activities carried out on the beaches, through a direct approach to those who frequent this environment, in addition, it was using data from historical series provided by BBMAr (Fire Brigade Maritimes of Maranhão). Despite the adversities and all the obstacles faced during the execution of the research, it was possible to locate with some drone overflights the place where the rip currents appeared along the main beaches of the state, identifying the points that could represent a real risk of drowning. and incidents for visitors to these beaches. This work serves as a starting point for further research to be carried out, since there is not an expressive number of works with this approach in Maranhão, precisely on the large island of São Luís. DOI:https://doi.org/10.56238/sevened2024.010-042